PLC-Based Pressure Control in Multi-Pump Applications - Vodovozov, Valery; Raud, Zoja; Gevorkov, Levon (Electrical, Control and Communication Engineering, 2015)
The paper is devoted to the centrifugal pumps represented the most popular type of pumping equipment used in different areas. The pressure control approach for variable speed driven (VSD) parallel connected centrifugal pumps is reported. The goal of the study is optimization of some quality indices, such as efficiency, consumed power, productivity, energy carrier temperature, heat irradiation, etc. One of them – efficiency – has been studied in the paper more carefully. The mathematical model of pumping process is discussed and a vector-matrix description of the multi-pump application is given. The program-based pressure control system is developed which productivity is changed by regulating the number of working pumps. The paper introduces new pressure control algorithms based on the working point estimation intended for programmable logical controllers (PLC). Experiments prove correctness of the offered methodology.